GAYA KEPEMIMPINAN KEPALA SEKOLAH PEREMPUAN: STUDI PADA SEKOLAH DASAR NEGERI DI SURABAYA (Lentera, Jurnal Studi Perempuan, 2010)
Abstract The purpose of this research is to describe Principal’s leadership slyle of women in Country Primary School in Surabaya. The total of the samples are 64 People. Data analysis is done cjiiantitatively asing analysis developed by the concept of Leadership Accuracy theory. reviewing to the Least Preferred Coworker (LPC) faetor in defining Leadership slyle and controlling leadership situalion consist ofLeader-Member Range Scale (UAR), Tas k Structure Range Scale (TSR), and Power Positioning Range Scale (PPR) to decide leadership effectiveness. This research is to reveal that large part of the women Principal has leadership slyle oriented to the relationship and an effective leader. Most ineffective leaders based on the concept of Leadership Accuracy theory have a qnite good performance. It is supported by the research finding before, ihal women leader has special strategy in her leadership. This strategy is lo invenl conductive circle of leadership in patriarch world. Keywords: Concept of Leadership Accuracy theory, Women Leadership. Leadership Slyle.